2007
DOI: 10.1097/smj.0b013e318158326f
|View full text |Cite
|
Sign up to set email alerts
|

Amebiasis Presenting as Acute Appendicitis

Abstract: Amebiasis presenting as acute appendicitis is extremely rare. The case of a 38-year-old Hispanic man who presented to the hospital with symptoms and signs suggestive of acute appendicitis is reported. He underwent laparoscopic appendectomy and the pathologic examination of the appendix revealed multiple trophozoites of Entamoeba histolytica. The patient was treated postoperatively with metronidazole for amebiasis, and follow-up stool studies showed no sign of residual infection. The patient has remained asympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Two of the early studies reported results from barium swallow radiography [39, 40], which was later replaced by imaging analysis. Among the seven patients with findings reported from ultrasonography and/or computed tomography scanning, acute appendicitis was diagnosed in four, periappendicular abscess in two, and a right abdomen lower quadrant mass in one [1, 2, 8, 9, 17, 18, 25]. The final diagnoses for the overall patients included acute appendicitis (167/172, 97.0 %), of whom 6 % had complicated acute appendicitis, including a periappendicular abscess, periappendicular mass, and perforated appendicitis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the early studies reported results from barium swallow radiography [39, 40], which was later replaced by imaging analysis. Among the seven patients with findings reported from ultrasonography and/or computed tomography scanning, acute appendicitis was diagnosed in four, periappendicular abscess in two, and a right abdomen lower quadrant mass in one [1, 2, 8, 9, 17, 18, 25]. The final diagnoses for the overall patients included acute appendicitis (167/172, 97.0 %), of whom 6 % had complicated acute appendicitis, including a periappendicular abscess, periappendicular mass, and perforated appendicitis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…No restrictions were made on language, country, or journal. A total of 171 articles were retrieved for review, and 42 articles [1–42] were selected for inclusion in the analysis (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Very rarely (<0.5% cases) [ 3 ], the disease takes a fulminant course leading to the development of fulminant necrotising amoebic colitis, which causes gangrenous necrosis of the involved large bowel. In most of the cases reported, only a segment of the large bowel was involved; the involvement of the whole of the large bowel, as in our case is very rare.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2006;Livingston, et. al., 2007;Thalayasingam, 1985) and bacteria such as Campylobacter, Brucella and Salmonella (Campbell LK et al, 2006;Chan, et al, 1983;Lau, et al, 2005;Pourbagher, et al, 2006) as well as parasites (Andrade, et al, 2007;Elazary, et al,. 2005;Gali, et.…”
Section: Introductionmentioning
confidence: 99%